Sustainable Waste Management Strategies for Effective Energy Utilization in Oman: A Review - Okedu, Kenneth E.; Barghash, Hind F.; Al Nadabi, Husam A. (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the adverse effect of energy production from traditional fossil fuels, the move towards renewable and sustainable energy has become imperative. The waste disposal sector offers hope towards environmental sustainability and potential to generate strong income for any economy. The region of the Gulf Cooperation Council (GCC) member countries in the Middle East generates the highest quantity of municipal waste per capita, compared globally to other countries. In the GCC region, waste is usually just dumped at different landfill stations. Effective waste management is imperative for environmental protection and sustainable development. This paper presents a review of the sustainable waste management strategies in Oman, in line with the United Nations goal on environmental management of waste. The current waste management strategies in Oman were discussed, and various Waste-to-Energy (WTE) technologies were proposed. These proposed WTE strategies would help in effective waste management in Oman and also in increasing the power grid capability. The salient part of this paper is an overview of the ability of using landfill leachate as feedstock to produce clean and green hydrogen gas considering different photo-fermentation processes. Production of hydrogen using single photo-fermentation process considering; landfill leachate alone, with leachate and addition of inoculum such as sewage sludge, and with substrate such as sucrose, glucose and landfill leachate utilizing batch bio-reactor and anaerobic conditions at controlled temperature, different initial pH, and heat treatment temperature range. Furthermore, a prototype model for the optimization of the inoculum size and the substrate was proposed considering 2-level factorial design using design expert. The data gathering of this paper was carried out by investigating the different regions in Oman having the lowest and highest waste produce, the average annual waste for the different governorates and the total amount of waste for five consecutive years (2015 to 2020), for the various engineered landfills. The cost of managing waste in the different governorates of Oman was presented, considering the average annual waste produced, in various regions of the country for the duration of the study. More so, some challenges and opportunities in carrying out effective waste management in Oman were addressed.